Gender features of oral speech in the Kazakh, English and German - Nurakhmetov, Е.Н.; Naraliyeva, А.А. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2018)
The article deals with the main differences of gender features of men’s and women’s oral speech. Currently, this research is one of the most interesting problems of gender differences between men’s and women’s speech, having their own characteristics and distinctive features. In addition to studying the general features of the men’s and women’s speech, much attention is paid to the development of the main theoretical positions of influence of the gender factor on the language. This research has given examples of gender characteristics in the Kazakh, English and German languages on the bases of lexical, phonetic and grammatical features.This article considered facts from life, customs, culture and features of oral speech of the Kazakh, English and German people as well as social factors and changes in the society.